An integrated petrological, geochemical and Re–Os isotope study of peridotite xenoliths from the Argyle lamproite, Western Australia and implications for cratonic diamond occurrences - Luguet A.; Jaques A.L.; Pearson D.G.; Smith C.B.; Bulanova G.P.; Roffey S.L.; Rayner M.J.; Lorand J.-P. (My University, 2009)
An integrated study of the petrology and Re–Os geochemistry of a suite of peridotite xenoliths, some carrying abundant diamonds, from the richly diamondiferous Argyle AK1 lamproite pipe provides definitive evidence for a depleted lithospheric root of Neoarchean age (TRD eruption ∼ 2.2–3.1 Ga) beneath the Proterozoic Halls Creek Orogen at the margin of the Kimberley Craton, Western Australia. The microdiamonds from the peridotitic xenoliths are similar in their properties to the minor population of small, commercial sized, peridotitic diamonds from Argyle, both formed in the Archean from isotopically mantle-like carbon. The major element bulk chemistry and mineral chemistry of the Argyle peridotites are slightly less depleted than Archean cratonic peridotites as a whole but similar to those reported from Neoarchean–Paleoproterozoic cratonic provinces. The Argyle peridotite xenoliths were derived from within the diamond stability field (1050–1300 °C and 4.9–5.9 GPa) near the base of the lithosphere (typically 160–200 km depth) with a geothermal gradient of 41.5 mW/m2. This thick diamondiferous lithosphere, estimated at up to 225 km thick from present day seismic S-wave tomography, appears to have persisted since the time of eruption of the Argyle lamproite (∼ 1180 Ma). The existence of late Archean age lithosphere beneath the Argyle diamond pipe, in a region where no crustal rocks of Archean age are known, suggests a decoupling of the crust and mantle in the region of the Halls Creek Orogen, perhaps as a consequence of Paleoproterozoic (∼ 1.85 Ga) reworking and/or subduction at the margin of the Kimberley Craton. The confirmation of an Archean lithospheric root beneath the Argyle pipe at the margin of the Kimberley Craton seemingly conforms with “Clifford's Rule”, regarding the restriction of economic diamond deposits to those underlain by Archean cratons. However, Argyle owes its rich diamond grades not to its Neoarchean mantle roots but to the presence of richly diamondiferous eclogitic material accreted to the craton root during the Proterozoic.
Keywords: peridotite xenoliths; lithosphere; diamond; craton; Re–Os dating; mobile belt; Argyle; Precambrian::Archean::Neoarchean; Докембрий::Архей::Неоархейская